Definitions of health and disease among physicians and Społem PSS employees - Domaradzki, Jan; Kordel, Piotr (Journal of Medical Science, 2017)
Aim. Definitions of health and disease play an important role in the organization and functioning of a health care system. The meanings attached to both phenomena also shape individual’s health behaviours and may be more important for their understanding that one’s social status. Thus, the aim of the study was to determine how the educational status and kind of work influence the concepts of health and disease. It also aimed to determine what criteria do physicians and Społem PSS employees use while talking about health and disease and whether lay concepts of health differ from their professional counterparts.Material and Methods. The research was carried out between May and August 2013 among one hundred physicians and one hundred Społem PSS employees. Thus, the results refer to people who are professionally active. Respondents were questioned via a structured questionnaire which contained questions on their self-definitions of health and disease and the criteria of their evaluation.Results. The research has revealed important differences in definitions of health and disease between physicians and clerks from Społem PSS. While physicians used a medical criterion to define health more often, Społem PSS employees defined it according to mixed and subjective criteria. As for disease, while respondents from both groups defined it mainly in medical criteria, all Społem PSS employees described it in pathological terms; physicians, however, defined it mainly as an abstract lack of well-being. On the other hand, many respondents understood both phenomena as multidimensional which proves that both terms contain many contradicting meanings and are difficult to articulate. Also among physicians, high tendency to overmedicalization of many phenomena was observed.Conclusions. It has been proven that educational status and kind of work influence the way people understand health and disease. Thus, this research may be useful for health education and in planning health promotion and preventive actions.
Keywords: disease; definitions of health and disease; health; physicians; sociology of health and illness; Społem PSS employees